NUEVOS TRILOBlTES DE LA FORMACION SURI (ORDOVICICO TEMPRANO) EN LA REGION DE CHASCHUIL, PROVINCIA DE CATAMARCA. IMPLICANCIAS BIOESTRATIGRAFICAS (Ameghiniana, 2013)
A new trilobite fauna from Suri Formation is here described. The fauna includes Annamitella longulosa n. sp., Merlinia zupaya n. sp., Merlinia megacantha (Leanza), Carolinites genacinaca Ross, Oopsites sp., Ampyx tinogastaensis n. sp. and Neseuretus (Neseuretus) chaschuilensis n. sp. The vertical range of the taxa enables the distinction of two trilobite associations. Both of them suggest a Middle Arenigian age. Thus H. megacantha Zone is here restricted to this age.